Shakuhachi / Tomonari Tsuchiya - Tomonari, Tsuchiya; Syed Mohammed, Sharifah Faizah (Universiti Teknologi MARA, 2017)
This event is part of the World Music History Lecture Series organized by Dr Sharifah Faizah Syed Mohammed.